Photoperiodic plasticity in circadian clock neurons in insects - Shiga, Sakiko (Frontiers in Physiology, 2013)
Since Bünning’s observation of circadian rhythms and photoperiodism in the runner bean Phaseolus multiflorus in 1936, many studies have shown that photoperiodism is based on the circadian clock system. In insects, involvement of circadian clock genes or neurons has been recently shown in the photoperiodic control of developmental arrests, diapause. Based on molecular and neuronal studies in Drosophila melanogaster, photoperiodic changes have been reported for expression patterns of the circadian clock genes, subcellular distribution of clock proteins, fiber distribution, or the number of plausible clock neurons in different species. Photoperiod sets peaks of per or tim mRNA abundance at lights-off in Sarcophaga crassipalpis, Chymomyza costata and Protophormia terraenovae. Abundance of per and Clock mRNA changes by photoperiod in Pyrrhocoris apterus. Subcellular Per distribution in circadian clock neurons changes with photoperiod in P. terraenovae. Although photoperiodism is not known in Leucophaea maderae, under longer day length, more stomata and longer commissural fibers of circadian clock neurons have been found. These plastic changes in the circadian clock neurons could be an important constituent for photoperiodic clock mechanisms to integrate repetitive photoperiodic information and produce different outputs based on day length.